INNOVATIVE MANAGEMENT IN THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES - A.B. Rakhisheva; R.B. Sartоva; B.Zh. Bolatova; Zh.M. Omarkhanova (Academic Journal of Physical and Chemical Sciences, 2019)
The article discusses innovation in small and medium-sized businesses, as well as features of innovation management. The innovative economy of any country is mainly determined by the presence of innovative organizations. The innovation of the organization depends on internal factors (this group includes, first of all, the potential and resources of the organization, intellectual capital, material, financial and organizational resources). In addition, the level of development of innovative activities of the organization depends on the characteristics of the industry and the sector in which the organization operates. External factors include: national conditions, such as legal acts related to the support of innovative activities or conditions for the development of innovations in a particular region, as well as legal, cultural, economic and technical factors.